Food aid cargo preference: Impacts on the efficiency and effectiveness of emergency food aid programs - Vincent H. Smith; Stephanie Mercier; Philip G. Hoxie (American Enterprise Institute (AEI), 2021)
This paper examines the impact of cargo preference requirements, which create market power for domestic shipping companies, on the effectiveness of USAID's Food for Peace emergency food aid program.
Keywords: A; 330; Agriculture; Economics; Mercantile Policy; Shipping; United States Agency For International Development (USAID)